Genetic diversity of Colombian sylvatic Trypanosoma cruzi isolates revealed by the ribosomal DNA - Patricia Cuervo; Elisa Cupolillo; Iris Segura; Nancy Saravia; Octavio Fernandes (Memorias do Instituto Oswaldo Cruz, 2002)
American trypanosomiasis is a common zoonosis in Colombia and Trypanosoma cruzi presents a wide distribution throughout the country. Although some studies based on enzyme electrophoresis profiles have described the population structure of the parasite, very few molecular analyses of genotipic markers have been conducted using Colombian strains. In this study, we amplified the non-transcribed spacer of the mini-gene by PCR, typing the isolates as T. cruzi I, T. cruzi zymodeme 3 or T. rangeli. In addition, the internal transcribed spacers of the ribosomal gene concomitant with the 5.8S rDNA were amplified and submitted to restriction fragment polymorphism analysis. The profiles were analyzed by a numerical methodology generating a phenetic dendrogram that shows heterogeneity among the T. cruzi isolates. This finding suggests a relationship between the complexity of the sylvatic transmission cycle in Colombia and the diversity of the sylvan parasites.